Answer:
6 and 3
Step-by-step explanation:
x^2 - 9x + 18 = 0
(x-6)•(x-3)=0
if x-6 = 0 then x = 6
and if x-3= 0 then x = 3
Answer:
The answer should be D. It is -2 on the inside because it is backwards of what you may think and because it is inside the square root. The -3 represents a down shift of 3
D : because this make so much since duh . && watch yuu get it right !
23. Kim and Jay leave at the same time to travel 25 miles going to the beach.
Kim drives 9 miles in 12 minutes
Jay drives 10 miles in 15 minutes.
Question: who will arrive first?
Unit rate of Kim
=> 9 miles in 12 minutes
=> 0.75 miles / minutes
=> 25 / 0.75
It will take 33.33 minutes for Kim to arrive
Unit rate of Jay
10 miles in 15 minutes.
=> 10 miles /15 minutes
=> 0.67 miles /minute
=> 25 / 0.67
It will take Jay 37.31 minutes to arrive at the beach.
SO Kim will arrive first